Insights Into the MYB-Related Transcription Factors Involved in Regulating Floral Aroma Synthesis in Sweet Osmanthus - Yan, Xin; Ding, Wenjie; Wu, Xiuyi; Wang, Lianggui; Yang, Xiulian; Yue, Yuanzheng (Frontiers in Plant Science, 2022)
As an important member of the MYB transcription factor (TF) family, the MYB-related transcription factors play multiple roles in regulating the synthesis of secondary metabolites and developmental processes, as well as in responding to multiple biotic and abiotic stresses in plants. However, little is known regarding their roles in regulating the formation of floral volatile organic compounds (VOCs). In this study, we conducted a genome-wide analysis of MYB-related proteins in sweet osmanthus; 212 OfMYB-related TFs were divided into three distinct subgroups on the basis of the phylogenetic tree. Additionally, we found that the expansion of the OfMYB-related genes occurred primarily through segmental duplication events, and purifying selection occurred in all the duplicated gene pairs. The RNA-seq data revealed that the OfMYB-related genes were widely expressed in different organs of sweet osmanthus, and some showed flower organ/development stage-preferential expression patterns. Here, three OfMYB-related genes (OfMYB1R70/114/201), which showed nuclear localization and were mainly expressed in the floral organs, were found to be significantly involved in regulating the synthesis of floral VOCs. Interestingly, only OfMYB1R201 had transcriptional activity, thus implying that this gene directly regulates the expression of VOCs synthesis related genes. Remarkably, the transient expression results suggested that OfMYB1R70, OfMYB1R114, and OfMYB1R201 are involved in the regulation of VOCs synthesis; OfMYB1R114 and OfMYB1R70 are involved in accelerating β-ionone formation. In contrast, OfMYB1R201 decreases the synthesis of β-ionone. Our results deepen our knowledge of the functions of MYB-related TFs and provide critical candidate genes for the floral aroma breeding of sweet osmanthus in the future.